Analysis of Multi-leaf Collimator (MLC) Usage on OAR (Organ at Risk) Dose Distribution with IMRT (Intensity Modulated Radiation Therapy) Technique in Nasopharyngeal Cases - Shadiqah Fitri; Saleha Saleha; Ayu Hardianti Pratiwi; Ajeng Anggreny Ibrahim; Sri Dewi Astuty; Syamsir Dewang (BULETIN FISIKA, 2025)
Nasopharyngeal cancer is one of the most prevalent types of cancer in Indonesia, accounting for 4.6% of cases according to the 2022 GLOBOCAN report, with radiotherapy using the IMRT technique being the primary treatment method. The MLC plays a crucial role in regulating radiation dose distribution, ensuring optimal dose delivery to the tumor while minimizing exposure to surrounding healthy organs, known as OAR. This study aims to analyze the impact of MLC usage on dose distribution to OAR, particularly the brainstem, chiasm, and spinal cord. This research was conducted through a secondary analysis of radiotherapy treatment planning data from 10 nasopharyngeal cancer patients using TPS at TK II Pelamonia Hospital in Makassar. The analyzed parameters include CI and HI to evaluate dose conformity and homogeneity within the target tumor, as well as the absorbed dose in OAR, which was compared against QUANTEC tolerance limits. The results indicate that CI and HI values fall within the recommended range, suggesting an optimal dose distribution to the target tumor. The maximum dose received by the brainstem and chiasm remained within the safe threshold (<54 Gy), while the spinal cord in two patients exceeded the recommended limit (<45 Gy) by 3.434 and 0.881 Gy. This discrepancy is attributed to factors such as tumor location and volume, anatomical variations among patients, and differences in MLC thickness. The use of MLC in IMRT planning effectively modulates dose distribution; however, further of various planning parameters is necessary in certain cases to ensure dose safety for specific OAR.